2019
DOI: 10.1097/md.0000000000017366
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for epidural morphine induced pruritus in parturients receiving cesarean section

Abstract: This study is designed to clarify the incidence of epidural morphine induced pruritus (EMIP) in Chinese Han and Tibetan parturients after cesarean section (CS) and to identify the correlated risk factors.This is a prospective multicenter observational study. Follow-up evaluations were performed at 3 hours, 6 hours, 12 hours, 24 hours, and 48 hours after morphine administration. The primary outcome was EMIP incidence. Other details were also recorded for risk factor screening.Totally 284 parturients receiving C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…[29] The potentiation of epidural analgesia when magnesium is used as adjuvant has been described in several reports. [30][31][32] In our study, patients who received magnesium sulphate during the operation showed to have less postoperative pain compared with patients who did not. These observations are in accordance with prior studies results on the analgesia-potentiating effect of magnesium.…”
Section: Discussionmentioning
confidence: 46%
“…[29] The potentiation of epidural analgesia when magnesium is used as adjuvant has been described in several reports. [30][31][32] In our study, patients who received magnesium sulphate during the operation showed to have less postoperative pain compared with patients who did not. These observations are in accordance with prior studies results on the analgesia-potentiating effect of magnesium.…”
Section: Discussionmentioning
confidence: 46%
“…Pruritus may occur 5.6±4.8 hours after the administration of morphine and can last for 14.0±8.8 hours. Also, Pettini et al (12) and Tan et al (13) reported a history of allergies is a potential risk factor for pruritus caused by morphine. Studies by Pettini et al (12) and Aly et al (14) have shown that serum serotonin levels are significantly increased in patients after cesarean section, and the absence of serotonin receptor antagonists is also a potential risk factor for pruritus.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless researchers continue to find the optimum adjuvants, as the currently researched adjuvants (e.g. opioids, tramadol, dexmedetomidine) still have some adverse effects such as nausea and vomiting, pruritus, bradycardia, and hypotension [4][5][6].…”
Section: Introductionmentioning
confidence: 99%